Invest, Hold Up, or Accept? China in Multilateral Governance. (2nd January 2016) - Kastner, Scott L.; Pearson, Margaret M.; Rector, Chad
Abstract : China has played an inconsistent role in multilateral governance, sometimes contributing to the creation and maintenance of international regimes, sometimes free riding or even threatening to undermine multilateral regimes to improve its position. We show that the strategic context of a particular issue of international concern affects China's approach to multilateralism and argue that our approach adds additional leverage to existing theories that rely on assumptions about its inherent disposition or socialization processes. An emerging global power will be willing to invest more in supporting a regime when its outside options are relatively poor. When its outside options are good, it will free ride on the efforts of more established states if it is not a necessary player in maintaining regimes, and if it is seen as indispensable it will threaten to hold up regime support as a way to win concessions. We show that these two factors, outside options and indispensability, can help explain changes in China's strategy with respect to the issue of North Korea's nuclear program and the regulation of international finance.